Udostępnianie wód termalnych w Uniejowie – rys historyczny - Sapińska-Śliwa, Aneta (Biuletyn Uniejowski, 2012)
The article presents the history of the exploitation of geothermal waters in Uniejów. Interest in the use of geothermal waters in the area Uniejów began in the late 1960s, whe the parameters of water examined during the drilling of the well Koło IG-3 were found to be satisfactory. The first hydrogeological well was drilled in Uniejów in 1978. The next two wells were drilled in the early 1990s as part of a large project, which aimed at creation of two doublets and multi-variant use of geothermal waters in Uniejów. Unfortunately, the opening of geothermal installations had to wait until the year 2001. The article also describes the current development of geothermal energy and water in Uniejów.